Pemanfaatan gasifikasi batubara untuk unit pengeringan teh - Ari Susandy Sanjaya; S Suhartono; Herri Susanto (Jurnal Teknik Kimia Indonesia, 2006)
Coal gasification utilization for tea drying unit. Anticipating the rise of fuel oil, the management of a tea plantation and drying plant has considered to substitute its oil consumption with producer gas (gaseous fuel obtained from gasification process). A tea drying unit normally consumes 70 L/h of industrial diesel oil and is operated 10 hours per day. The gasification unit consisted of a down draft fixed bed gasifier (designed capacity of about 100 kg/h), gas cooling and cleaning systems. The gas producer was delivered to the tea processing unit and burned to heat the drying oil: Low calorific value coal (4500 kcal/kg) and wood waste (4000 kcal/kg) have been used as fuel. The gasification unit could be operated as long as 8 hours without refueled since the coal hopper on the toppart of gasifier has a capacity of 1000 kg. Sometimes, the gasification process must be stopped before coal completely consumed due to ash melting inside the gasifier. Combustion of producer gas produced a pale-blue flame, probably due to a lower calorific value of the producer gas or too much excess air. Temperature of heating-air heated by combustion of this producer gas was only up to 96 oC. To achieve the target temperature of 102 oC, a small oil burner must he operated at a rate ofabout 15 L/h. Thus the oil replacement was about 78%.Keywords:  Fuel oil, Producer gas, Downdraft gasifier, Dual fuel, Calorific value, Burner. AbstrakKenaikan harga bahan bakar minyak untuk industri pada awal 2006 telah mendorong berbagai pemikiran dan upaya pemanfaatan bahan bakar alternatif. Sebuah unit gasifikasi telah dipasang di pabrik teh sebagai penyedia bahan bakar alternatif. Unit gasifikasi tersebut terdiri dari gasifier, pendingin, pembersih gas, dan blower. Unit gasifikasi ini ditargetkan untuk dapat menggantikan konsumsi minyak bakar 70 L/jam. Gasifier dirancang untuk kapasitas 120 kg/jam batubara, dan memiliki spesifikasi sebagai berikut: downdraft gasifier; diameter tenggorokan 40 cm, diameter zona reduksi 80 cm. Bunker di bagian atas gasifier memiliki kapasitas sekitar 1000 kg batubara agar gasifier dapat dioperasikan selama 8 jam tanpa pengisian-ulang. Bahan baku gasifikasi yang telah diuji-coba adalah batuhara kalori rendah (4500 kcal/kg) dan limbah kayu (4000 kcal/kg). Gas produser (hasil gasifikasi) dibakar pada burner untuk memanaskan udara pengering teh sampai temperatur target 102 oC. Pembakaran gas produser ternyata menghasilkan api biru pucat yang mungkin disebabkan oleh rendahnya kalor bakar gas dan tingginya udara-lebih. Temperatur udara pengering hasil pemanasan dengan api gas produser hanya mencapai 96 oC. Dan untuk mencapai temperatur udara pengering 102 oC, burner gas prod user harus dibantu dengan burner minyak 15 L/jam. Jadi operasi dual fued ini dapat memberi penghematan minyak bakar 78%.Kata kunci: Minyak bakar, Gas produser, Downdraft gasifier, Dual fuel, Kalor bakar, Burner.